2018
DOI: 10.1007/978-3-319-93888-2_1
|View full text |Cite
|
Sign up to set email alerts
|

Using the Ideas Café to Explore Trust in Autonomous Vehicles

Abstract: Trust has been shown to play a key role in our ability to safely use autonomous vehicles; hence the authors used the Ideas Café to explore the factors affecting trust in autonomous vehicles. The Ideas Café is an informal collaborative event that brings the public together with domain experts for exploratory research. The authors structured the event around factors affecting trust in the technology, privacy and societal impact. The event followed a mixed methods approach using: table discussions, spectrum lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Furthermore, it has been previously found that participants require clear communication of a vehicle's capabilities [11]; specifically the communication of technical competence, by explaining what the vehicle is doing and why, has been found to be effective [61], [62]. The results from this study confirm that participants consistently fixated on information that provided an explanation as to what the vehicle was doing and why it was doing it.…”
Section: ) Overall Fixations To Information Iconssupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, it has been previously found that participants require clear communication of a vehicle's capabilities [11]; specifically the communication of technical competence, by explaining what the vehicle is doing and why, has been found to be effective [61], [62]. The results from this study confirm that participants consistently fixated on information that provided an explanation as to what the vehicle was doing and why it was doing it.…”
Section: ) Overall Fixations To Information Iconssupporting
confidence: 73%
“…This poor efficiency when monitoring an automated process has been attributed to an increase in the cognitive complexity of using the vehicle for the user, as the driver is required to understand the vehicle's intention, predict future actions and continuously make judgements as to whether an intervention is required [8], [9]. Designing HMIs that are able to communicate effectively with the driver can be a positive influence on driver's use of an automated vehicle [10], [11], by enabling drivers to develop accurate mental models of the vehicle's intended actions [12]. However, there is some preliminary evidence to suggest that interfaces in partially automated vehicles today are not effective.…”
Section: Introductionmentioning
confidence: 99%
“…This is because they perceived there to be greater comfort in a "human override" mode due to the idea of better performance of humans in impulsive situations. Conversely, individuals who preferred private ownership of AVs believed that they could be safer than conventional vehicles [167][168][169][170].…”
mentioning
confidence: 99%
“…Data privacy was seldom mentioned by our participants, but it still poses a risk since every activity in connected and AVs can potentially be recorded and consequently seen by other parties. When prompted, people can discuss about a number of issues such as hacking of AVs [61]. The design and manufacture of the car of the future should take in consideration concerns related to privacy and security, which seems to be largely neglected by the Automotive UI community [31].…”
Section: Discussionmentioning
confidence: 99%